2019
DOI: 10.1002/mrm.27635
|View full text |Cite
|
Sign up to set email alerts
|

Simian immunodeficiency virus transiently increases brain temperature in rhesus monkeys: detection with magnetic resonance spectroscopy thermometry

Abstract: Purpose To evaluate brain temperature effects of early simian immunodeficiency virus (SIV) infection in rhesus macaques using proton magnetic resonance spectroscopy (MRS) thermometry (MRSt) and to determine whether temperature correlates with brain choline or myo‐inositol levels. Methods Brain temperature was retrospectively determined in serial MRS scans that had been acquired at baseline and at 2 and 4 weeks post‐SIV infection (wpi) in 16 monkeys by calculating the chemical shift difference between N‐acetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The authors have experimentally shown that, with respiratory gating and motion compensation, but without bowel filling, the standard deviation may amount to about 10 C in the pancreas head, which would lead to problems in treatment evaluation and safety monitoring during thermal therapy. Filling the bowel through oral intake of 500 mL fluid increased the precision to 2 C. (Pineapple juice was chosen because of its high manganese content leading to short relaxation times, as had been demonstrated previously [Arthurs et al, 2014] (Mintzopoulos et al, 2019). Here, the chemical-shift difference between the methyl resonance of NAA and the water proton resonance was used to calculate absolute temperature for each voxel.…”
Section: The Methodological Groundwork: Advances In Mrs and Mri Temperature Methodsmentioning
confidence: 99%
“…The authors have experimentally shown that, with respiratory gating and motion compensation, but without bowel filling, the standard deviation may amount to about 10 C in the pancreas head, which would lead to problems in treatment evaluation and safety monitoring during thermal therapy. Filling the bowel through oral intake of 500 mL fluid increased the precision to 2 C. (Pineapple juice was chosen because of its high manganese content leading to short relaxation times, as had been demonstrated previously [Arthurs et al, 2014] (Mintzopoulos et al, 2019). Here, the chemical-shift difference between the methyl resonance of NAA and the water proton resonance was used to calculate absolute temperature for each voxel.…”
Section: The Methodological Groundwork: Advances In Mrs and Mri Temperature Methodsmentioning
confidence: 99%
“…Indeed, brain-derived EVs have been purified from cultured neurons, oligodendrocytes, microglia, astrocytes, and cerebrospinal fluid (CSF) [50][51][52]. However, there are no available studies describing the properties and functions of EVs from the basal ganglia (BG), a series of interconnected subcortical nuclei and a major target/ reservoir of HIV in the CNS [5,6]. BG dysfunction is a hallmark of HIV infection and cognitive impairment in PLWH with neuronal death in the BG [53].…”
Section: Introductionmentioning
confidence: 99%